Assessment of Presence of Cardiovascular Disease in Relation to Smoking - Rajiv Arora (Asian Journal of Medical Research, 2019)
Background: Smoking is a major risk factor for the development and progression of cardiovascular diseases. Thus, the present study investigates presence of cardiovascular disease in relation to smoking in people aged 45-50 years. Subjects and Methods: This cohort study was conducted among 40 people of age 45-50 years over the period of 6 months. All relevant clinical history was taken before the commencement of the study. Statistical analysis was done by using   SPSS, version 15 (SPSS, Inc., Chicago, IL) and  p<0.05 was considered statistically significant. Results: In our study total participants were 40 in which 27 were male and 13 were females. In our study 18 men were recent smoker and 9 were ex-smoker. In females 8 were recent smoker whereas 5 were ex-smoker. 13 recent and 5 ex-smoker men had cardiovascular disease whereas 7 recent and 5 ex-smoker women had cardiovascular disease. Conclusion: The results of this study reinforce that smoking is a significant factor in causation of cardiovascular disease. Thus, we have to make strategies for smoking cessation programs in the primary care setting.